Carbon Leakage : Theory, Evidence and Policy Design - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
Carbon leakage is much discussed in carbon pricing policy. Stakeholders, especially emissions-intensive industries, have expressed concern about the implications of carbon pricing when they compete with firms located in jurisdictions without equivalent policies. This technical note provides an overview of the issue of carbon leakage, discussing the theory, evidence and policy design. This issue is of interest to a range of PMR countries and is of great importance to successful design and implementation of carbon pricing policies. The technical note addresses three broad questions: – How to evaluate the expected competitiveness and carbon leakage impacts (negative and positive) due to carbon pricing policies for different sectors and the entire economy? – How to mitigate the risk of negative impacts and strengthen the positive impacts (through instrument design or complementary policies) in the short and long term, and for different levels of expected decarbonization? – How to manage the process of dialogue between a government, business and civil society on the implications for competitiveness and risks of carbon leakage, and their mitigation? It draws lessons from policymaking experience and academic evidence to provide guidance to countries on how to address issues of carbon leakage as they arise in their national contexts.